Literasi kesehatan untuk anak usia dini melalui kegiatan healthy drinks - Mala, Lilik Sofwatul; Farunnisa , Farunnisa; Hayati, Kulsum Nur (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2025)
Health literacy from an early age plays an important role in shaping a healthy lifestyle for children. One aspect that needs to be introduced is an understanding of healthy drinks in order to build good consumption habits. This study aims to analyze the implementation of health literacy activities through the introduction and practice of consuming healthy drinks in early childhood. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The subjects of the study consisted of 25 early childhood education institutions (PAUD), namely RA Masyithoh Wareng Butuh Purworejo who participated in health literacy activities for one month. Data were analyzed using thematic analysis techniques to understand children's consumption patterns and responses to various types of healthy drinks that were introduced. The results showed that of the 25 children who participated, 95% preferred fruit juice, 75% did not like ginger wedhang, 80% preferred turmeric and tamarind herbal tea, and 100% preferred milk. This activity not only increased children's understanding of the benefits of healthy drinks but also created a fun learning experience. Children's enthusiasm increased as they tried various nutritious drinks and actively participated in activities. In conclusion, the implementation of health literacy through healthy drinks activities is effective in increasing early childhood awareness of the importance of healthy drink consumption patterns. It is hoped that this activity can be widely implemented to build a foundation for a healthy lifestyle from an early age.